Gender and its Relevance to Macroeconomic Policy : A Survey - Stotsky, Janet (Washington, D.C. : International Monetary Fund, 2006)
This survey examines the implications of gender differences in economic behavior for macroeconomic policy. It finds that reducing gender inequality and improving the status of women may contribute to higher rates of economic growth and greater macroeconomic stability. Women's relative lack of opportunities in developing countries inhibits economic growth, while, at the same time, economic growth leads to a reduction in their disadvantaged condition. Equality of opportunity in labor and financial markets is critical to enabling women to take full advantage of improved macroeconomic conditions. Macroeconomic policies should take into account the benefits of reducing gender inequalities, especially in the lowest-income countries where these differences are most pronounced, and should consider the potentially harsher short-term effects of economic austerity measures on women to avoid exacerbating gender inequalities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet